From Husserl to Levinas: The Role of Hyletic Data, Attachment, Emotion and the Other in Temporality - Poleščuk, Irina (Problemos, 2009)
This article discloses the question of the pre-giveness of the other and alterity by analyzing and comparing the temporality of consciousness and the role of affection and sensation in Husserl and Levinas.I argue that within the intentional flow of consciousness one can find non-intentional structures, i.e. affection and hyletic data which mark a passivity of consciousness, break intentional act and welcome the other. While discussing the temporal structure of consciousness the special attention is given to the discussion of pra-impression.
Keywords: Husserl; Levinas; temporality of consciousness; intentionality; affection; hyletic data; sensation